2020
DOI: 10.1186/s41938-020-00307-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of abamectin on lesser grain borer, Rhyzopertha dominica F. (Coleoptera: Bostrichidae), infestation on some stored grains

Abstract: Background Modern methods of stored wheat grain protection from insect pests strive towards optimizing the use of different techniques and methods within integrated pest management (IPM) programs. One of the methods of integral grain protection is the application of natural originating insecticides. Main body The potential of the natural origin synthetic insecticide abamectin (a product of soil bacteria, Streptomyces avermitilis fermentation) on the grain borer, Rhyzopertha dominica F. (Coleoptera: Bostrichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The host preference and mechanism of host selection by R. dominica should also be further studied (Perišić et al . 2018). Other studies have shown that temperature, humidity, and other biological/abiotic factors can affect the development, survival, and oviposition rate of R. dominica (Toews et al .…”
Section: Discussionmentioning
confidence: 99%
“…The host preference and mechanism of host selection by R. dominica should also be further studied (Perišić et al . 2018). Other studies have shown that temperature, humidity, and other biological/abiotic factors can affect the development, survival, and oviposition rate of R. dominica (Toews et al .…”
Section: Discussionmentioning
confidence: 99%
“…This potentiation may be since both pesticides have different modes of action; thus, their activities would complement each other in killing the larvae. Abamectin acts as an agonist for GABA receptors in nervous systems [ 51 , 52 ]. In comparison, chlorfenapyr offers a novel insecticidal mechanism based on its metabolites’ capacity to impede ATP generation in insect body cells [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was attacked by both field and also storage conditions by many insect pests. Among the pests, it is a very dangerous and harmful primary pest that can able to infest all types of cereals (Perisic et al, 2020). The insect readily infests storage grains and can cause economic losses throughout much of the world due to its high potential viability and adaptability (Scheff et al, 2022).…”
mentioning
confidence: 99%